Absent or Mild Coronary Calcium Predicts Low-Risk Stress Test Results and Outcomes in Patients Considered for Flecainide Therapy. (November 2021) - Anderson, Jeffrey L.; Knight, Stacey; McCubrey, Raymond O.; May, Heidi T.; Mason, Steve; Bunch, Thomas J.; Min, David B.; Cutler, Michael J.; Le, Viet T.; Muhlestein, Joseph B.; Knowlton, Kirk U.
Background: Flecainide is a useful antiarrhythmic for atrial fibrillation (AF). However, because of ventricular proarrhythmia risk, a history of myocardial infarction (MI) or coronary artery disease (CAD) is a flecainide exclusion, and stress testing is used to exclude ischemia. We assessed whether absent/mild coronary artery calcium (CAC) can supplement or avoid the need for stress testing. Methods: We assessed ischemic burden using regadenoson Rb-82 PET/CT in 1372 AF patients ≥50 years old without symptoms or signs of clinical CAD. CAC was determined qualitatively by low dose attenuation computed tomography (CT) (n = 816) or by quantitative CT (n = 556). Ischemic burden and clinical outcomes were compared by CAC burden. Results: Patients with CAC absent or mild (n = 766, 57.2%) were younger, more frequently female, and had higher BMI but lower rates of diabetes, hypertension, and dyslipidemia. Average ischemic burden was lower in CAC-absent/mild patients, and CAC-absent/mild patients showed greater coronary flow reserve, had fewer referrals for coronary angiography, and less often had obstructive CAD. Revascularization at 90 days was lower, and the rate of longer-term major adverse cardiovascular events was favorable. Conclusions: An easily administered, inexpensive, low radiation CAC scan can identify a subset of flecainide candidates with a low ischemic burden on PET stress testing that rarely needs coronary angiography/intervention and has favorable outcomes. Absent or mild CAC-burden combined with other clinical information may avoid or complement routine stress testing. However, additional, ideally randomized and multicenter trials are indicated to confirm these findings before replacing stress testing with CAC screening in selecting patients for flecainide therapy in clinical practice.